Interethnic relations in BH – sociological context (Религиски дијалог и соработка, 2020)
The paper is based on the research of interethnic relationsin BH society, cold interethnic relations caused by ethnic distance.Bosnia and Herzegovina, as a union of differences, a countrywhere three majority, or constitutive, nations merge and interactis a suitable ground for emergence of social distance based on thenegative ethnic and national characteristics and attitudes whichare ascribed to other peoples and which develop due to negativeopinion and antipathy towards other ethnic groups. The analysisincludes members of three constitutive peoples, Serbs, Croatsand Bosniaks, three different ethnic groups that share a commoncountry and territory, but have different cultural heritage. Theprimary aim of the study was to show ethnic distance based onthe level of kinship that the members of one ethnic group is readyto achieve with the members of other ethnic groups, multiethnicrelations within this society, as well as the influence of ethnic andnational prejudices on social distance or closeness. Today, stableethnic relations are an important factor of stability and security inmany countries and societies. Just like every ethnic group endeavorsto achieve its individual and collective rights, especially minoritygroups, so the countries try to achieve stable interethnic relationswithin, as well as utmost security and stability. The countries fromthis region burdened with tumultuous past and ethnic conflictsare trying to achieve the greatest stability and security possiblewhich is the reason they pay a special attention to the question ofregulating their ethnic relations.